Becoming an adolescent mother: The experiences of young Indonesian new mothers living with their extended families. (January 2022) - Erfina Erfina,; Widyawati Widyawati,; McKenna, Lisa; Reisenhofer, Sonia; Ismail, Djauhar
Abstract: Objective: Adolescent motherhood brings many challenges. While much is written about young mothers' transition to motherhood and their support needs, there is little from South-East Asian countries such as Indonesia. The aim of this study was to understand the new motherhood experiences of Indonesian adolescent females living with their extended families. Design: Eleven semi-structured interviews were conducted with new adolescent mothers. Setting: a large women and children's hospital in Makassar, South Sulawesi, Indonesia. Participants: Purposive sampling was undertaken. Eleven adolescent mother participated in this study. The mean age of the mothers was 17 years, ranging from 16 to 19 years of age. Findings: Four themes emerged: demonstrate transfer of knowledge between generations, sharing tasks with extended family, feeling blessed with extended family and local myth and cultural practice related to caring for the baby. Findingsdemonstrated that transfer of knowledge between generations was important for these adolescent mothers. They shared responsibilities with and felt blessed having their extended families, along with local beliefs and cultural practice related to caring fortheir babies. Discussion and implications for practice: Our findings contribute to understandings of experiences to becoming mothers among Indonesian adolescents living with extended family. Results can be used by healthcare providers, especially nurses and midwives, to develop cultural care interventions and educational program for maternity and psychosocial care for adolescent mothers and their families towards success in the transition period and maternal role attainment.